Macroeconomic implications of time-varying risk premia - François Gourio (European Central Bank (ECB), 2012)
A large empirical literature suggests that risk premia on stocks or corporate bonds are large and countercyclical. This paper studies a simple real business cycle model with a small, exogenously time-varying risk of disaster, and shows that it can replicate several important facts documented in the literature. In the model, an increase in disaster risk leads to a decline of output, investment, stock prices, and interest rates, and an increase in the expected return on risky assets. The model matches well business cycle data and asset price data, and the countercyclicality of risk premia. I present an extension of the model with endogenous choice of leverage and endogenous default, and show that the model accounts well for the level and cyclicality of credit spreads, and in particular the relation between investment and credit spreads.
Keywords: E32; E44; G12; 330; business cycles; credit spreads; Investment; rare events; risk premia